Treating Gastric Antral Vascular Ectasia: When Argon Therapy Is Not Enough - Castro,Francisca Dias de (2016)
Gastric antral vascular ectasia (GAVE) is a capillary-type vascular malformation of the gastric antrum and an infrequent cause of chronic gastrointestinal blood loss and iron deficiency anemia. The authors describe a case report of GAVE in a female cirrhotic patient presenting with severe symptomatic iron deficiency anemia. After failure of argon plasma coagulation (APC), the patient was treated with endoscopic band ligation (EBL) with resolution of anemia, without new episodes of rebleeding and no need for further hospitalizations or transfusion requirements. Even though APC is the current treatment of choice for GAVE recurrence-free survival at one year is achieved in less than 50% of the patients and failed therapy has been described in up to 14% of the patients. EBL has been reported to be a relatively easy technique for GAVE therapy and has been shown to be safe and effective with lower complication rates in comparison with APC. This technique may in the future be used as the initial endoscopic treatment to eradicate GAVE.